PERANCANGAN SISTEM REGENERASI OTOMATIS SILICA GEL PADA DEYHDRATING BREATHER TRAFO DENGAN METODE PROTOTYPE STUDI KASUS GARDU INDUK SURALAYA - Ahmad Rufai Rufai; Adith Aulia Rachman; Ovan Ady Santoso (LPPM Unbaja, 2026)
Transformers are crucial components in power systems whose reliability depends on the quality of insulating oil. One of the main problems is silica gel saturation in dehydrating breathers, which are still manually regenerated. This manual process is time-consuming and labor-intensive, and risks degrading the quality of the insulating oil if done too late, which can shorten the transformer's lifespan and increase maintenance costs. This study aims to design an automatic silica gel regeneration system for dehydrating breathers using a prototype method. This system uses an ESP32 microcontroller as the control center, a TCS3200 color sensor to detect silica gel saturation, a DHT22 sensor to measure temperature and humidity, and a heater controlled via a relay. The system is also integrated with the Internet of Things (IoT)-based Blynk application for remote monitoring. The results show that the designed automatic regeneration system successfully achieves all research objectives. The prototype is able to regenerate silica gel automatically and efficiently, detect color changes accurately, and display monitoring data in real-time through the Blynk application. This system is more effective than manual methods, minimizes maintenance delays, and improves transformer reliability at the Suralaya Substation